A Toxicological Safety Assessment of a Standardized Extract of Eulophia macrobulbon in Rodents - Preedapirom, Watcharaporn; Changwichit, Kanokwan; Tangchang, Warisaraporn; Ingkaninan, Kornkanok; Taepavarapruk, Pornnarin (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
The tuber of Eulophia macrobulbon (EM) has been traditionally used in Thailand to relieve pain and fatigue. Recently, it has been reported that EM extract could provide benefits such as anti-inflammatory, and antioxidant that may be used as herbal remedy in the pharmaceutical or food industries. Cytotoxic properties of EM extract on cancer cell lines were also reported in vitro . However, as yet, no safety data has been investigated. Our study is the first one in which the acute and chronic toxicity of the standardized extract of EM has been tested. The OECD Guideline No. 420 (limit test) was used for the acute toxicity test in which a single oral dose of 2000 mg crude extract/kg body weight was administered to Wistar rats. Observations were conducted during the 2-week period after administration. Clinical signs and mortality were used as parameters to evaluate the acute toxicity. The results showed no toxicity in terms of general behavior change, mortality, or change in gross appearance of internal organs. Chronic toxicity was studied by following OECD Guideline No. 452. EM extract was administered orally at doses of 5, 50 and 500 mg/kg for 6 months. Mortality, clinical signs, body weights, biological and hematological parameters, organ weights, as well as macro-and microscopic observation of several organs were evaluated at the end of the test period. Our tests showed that EM extract did not induce death or adverse effects, and nor did produce any abnormality of the hematological and biochemical parameters or histopathological changes. Overall, our test results have indicated that the oral Lethal Dose 50 (LD 50 ) of EM extract is more than 2,000 mg/kg, and oral administration of EM for long period up to 6 months is safe. Based on established literature on health benefits of EM, it is important to focus attention on its active constituents and therapeutic effects in order to further develop EM as herbal remedy for treating of inflammations associated diseases as well as erectile dysfunction. Keywords: Eulophia macrobulbon , Toxicological safety assessment, Acute and Chronic toxicity, rodents